Pengaruh Kepercayaan dan Pengetahuan Produk Terhadap KEPUTUSAN Pembelian Produk Kecantikan - Risnawati Risnawati; Almansyah Rundu Wonua; Niar Astaginy (Pusat Riset dan Inovasi Nasional, 2023)
This research aims to determine: (1) The influence of consumer trust on decisions to purchase beauty products (Case Study of Wardah Products at the Alke Cosmetic Store in Kolaka Regency) and (2) The Influence of Product Knowledge on Decisions to Purchase Beauty Products (Case Study of Wardah Products at the Alke Store Cosmetics in Kolaka Regency). This research is quantitative research with an explanatory research model using a questionnaire as the instrument. The population in this study were all Muslim female consumers using Wardah in Kab. Kolaka with a sample size of 120 respondents using observation, documentation and questionnaire techniques. Data collection techniques are primary data and secondary data. Research instrument testing uses validity and reliability tests with SPSS 25. Research data analysis techniques use the Structural Equation Modeling (SEM-PLS) method with SmartPLS 3.0. Based on the research results, it is known that consumer trust has a positive and significant effect on purchasing decisions. This is proven by the t-count or t-statistic which is 2.664 which is higher than the t-table value > 1.657. With P-values ​​0.009. Meanwhile, Product Knowledge also has a positive and significant effect on Consumer Purchasing Decisions because the t-count or t-statistic value is 4.797 which is higher than the t-table value >1.657 with P-values ​​of 0.000. So Consumer Trust and Product Knowledge have a positive and significant effect on Purchasing Decisions by 92.7%.